Factors influencing consumers' knowledge towards contaminated peanut-based products - Hassan, Nur Adibah; Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Food products contamination has become a huge global issue, mostly related to foodborne diseases. Morbidity and mortality are on the increase worldwide due to the increasing incidence of foodborne diseases. Peanut-based products are reported to contribute significantly to food contamination issues. It needs to be addressed well to make sure consumers are safe from these hazards. Besides, all of the scientific knowledge of food products contaminations symptoms needs to be known not only among scientists but also among consumers. Thus, the objectives of this study are to examine consumers’ knowledge level towards contaminated peanut-based products and to determine factors influencing consumers’ knowledge towards consuming contaminated peanut-based products. A survey using a structured questionnaire was carried out among 1,263 respondents who consumed peanut and peanut-based products in daily, weekly or monthly diet at Klang Valley area. The results from this study showed that about 73.9% of total respondents have inadequate knowledge and only 26.1% have adequate knowledge towards the issue of contaminated peanut-based products. The results also indicated that there are five factors (mass media, practicing standard, packaging information, experience, and official government website) that greatly influenced consumers’ knowledge towards the issue of contaminated peanut-based products. Consumers who have lack knowledge of the danger in consuming contaminated peanuts-based products are at risk of adverse health effects if consumed in a long term. Hence, the government and NGOs need to carry out campaigns that would increase awareness among consumers towards the risks of consuming contaminated peanut-based products.